Editor's Choice - Acute Cardiovascular Care Association Position Paper on Intensive Cardiovascular Care Units: An update on their definition, structure, organisation and function. Issue 1 (1st February 2018) - Bonnefoy-Cudraz, Eric; Bueno, Hector; Casella, Gianni; De Maria, Elia; Fitzsimons, Donna; Halvorsen, Sigrun; Hassager, Christian; Iakobishvili, Zaza; Magdy, Ahmed; Marandi, Toomas; Mimoso, Jorge; Parkhomenko, Alexander; et al.
Abstract: Acute cardiovascular care has progressed considerably since the last position paper was published 10 years ago. It is now a well-defined, complex field with demanding multidisciplinary teamworking. The Acute Cardiovascular Care Association has provided this update of the 2005 position paper on acute cardiovascular care organisation, using a multinational working group. The patient population has changed, and intensive cardiovascular care units now manage a large range of conditions from those simply requiring specialised monitoring, to critical cardiovascular diseases with associated multi-organ failure. To describe better intensive cardiovascular care units case mix, acuity of care has been divided into three levels, and then defining intensive cardiovascular care unit functional organisation. For each level of intensive cardiovascular care unit, this document presents the aims of the units, the recommended management structure, the optimal number of staff, the need for specially trained cardiologists and cardiovascular nurses, the desired equipment and architecture, and the interaction with other departments in the hospital and other intensive cardiovascular care units in the region/area. This update emphasises cardiologist training, referring to the recently updated Acute Cardiovascular Care Association core curriculum on acute cardiovascular care. The training of nurses in acute cardiovascular care is additionally addressed. Intensive cardiovascular care unit expertise is not limited to within the unit's geographical boundaries, extending to different specialties and subspecialties of cardiology and other specialties in order to optimally manage the wide scope of acute cardiovascular conditions in frequently highly complex patients. This position paper therefore addresses the need for the inclusion of acute cardiac care and intensive cardiovascular care units within a hospital network, linking university medical centres, large community hospitals, and smaller hospitals with more limited capabilities.